The 1975 Japanese diet has a stress reduction effect in mice: search for physiological effects using metabolome analysis. Issue 4 (3rd April 2018) - Iwagaki, Yui; Sugawara, Saeko; Huruya, Yasuhisa; Sato, Miki; Wu, Qiming; E, Shuang; Yamamoto, Kazushi; Tsuduki, Tsuyoshi
Abstract: We aimed to find new physiological effects of the Japanese diet. First, to determine the key components in serum from mice fed the 1975 diet, serum from mice fed the 1960, 1975, 1990 or 2005 Japanese diet was analyzed using CE-TOFMS and LC-TOFMS. Based on these results, the key components were determined by principal component analysis. Among the identified compounds, GABA was included. Therefore, a stress reduction effect was inferred as a novel physiological effect of this diet. Next, we tested whether the 1975 diet had an actual stress reduction effect in mice. Mice were given the 1975 diet or a control diet for 4 weeks, after which they were divided into restraint stress and non-stress groups. Mice fed the 1975 diet had significantly decreased stress parameters compared with those fed the control diet. These results provide the first evidence that the 1975 Japanese diet has a stress reduction effect. Abstract: : In the current study, we aimed to find new physiological effects of the Japanese diet. As a result, we found that the 1975.